2017
DOI: 10.1590/2359-3997000000305
|View full text |Cite
|
Sign up to set email alerts
|

Obese with higher FNDC5/Irisin levels have a better metabolic profile, lower lipopolysaccharide levels and type 2 diabetes risk

Abstract: Objective: Thus, the aim of this study was to compare if higher or smaller fibronectin type 3 domain-containing protein 5 (FNDC5)/irisin levels are associated with inflammatory and metabolic markers, caloric/macronutrient intake, physical fitness and type 2 diabetes mellitus (T2DM) risk in obese middle-aged men, and also to correlate all variables analyzed with FNDC5/irisin. Subjects and methods: On the basis of a cluster study, middle-aged obese men (IMC: 31.01 ± 1.64 kg/m²) were divided into groups of higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 38 publications
0
24
0
2
Order By: Relevance
“…20 , 22 Irisin levels paralleled body weight reduction after weight-loss by either dietary or surgical treatment, and restored after regaining the lost weight, 13 which revealed that irisin strongly reflects adiposity and body fat mass. But there are also the opposite conclusions concerning the relation between the circulating irisin and obesity, studies of Korean prepubertal children 8 and Brazil obese middle-aged men 23 observed inverse correlations between irisin and body mass index, a study in Chinese adults also indicated that serum irisin were correlated negatively with BMI, and was a predictor of insulin resistance. 7 The results about correlation between circulating irisin and obesity was still controversial, especially in the eastern-Asian population.…”
Section: Discussionmentioning
confidence: 99%
“…20 , 22 Irisin levels paralleled body weight reduction after weight-loss by either dietary or surgical treatment, and restored after regaining the lost weight, 13 which revealed that irisin strongly reflects adiposity and body fat mass. But there are also the opposite conclusions concerning the relation between the circulating irisin and obesity, studies of Korean prepubertal children 8 and Brazil obese middle-aged men 23 observed inverse correlations between irisin and body mass index, a study in Chinese adults also indicated that serum irisin were correlated negatively with BMI, and was a predictor of insulin resistance. 7 The results about correlation between circulating irisin and obesity was still controversial, especially in the eastern-Asian population.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our results also demonstrated increased resistin levels in obese children and in those with MS compared with control children, which is expected in obesity, as well as a negative correlation between irisin and resistin. A single study in a cohort of children has reported no correlation between irisin and resistin [48], while in obese men, a tendency toward decreased resistin levels along with higher levels of irisin has been described [58]. Similarly, in an animal model, rats exposed to exercise exhibited increased PGC-1α and irisin but decreased resistin expression [59].…”
Section: Discussionmentioning
confidence: 99%
“…Basic and clinical studies in adults have found diverse associations between irisin and adipokines. A positive association between irisin and leptin [52] and adiponectin [53] has been described, while a negative relationship of irisin with leptin [54, 55], adiponectin [35, 56, 57], and resistin [58, 59], or no correlation with any of them have also been found [48, 60, 61]. Noteworthy, studies associating irisin concentrations with the different adipokines in the pediatric population are both limited and contradictory [42], and to date, no data has been found for adipsin.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the lower concentration of irisin in the blood of patients with type 2 diabetes compared to healthy people, they revealed the negative correlations with creatinine, systolic, and diastolic blood pressure, BMI, ACR, and HbA1c [ 55 ]. Bonfante et al [ 56 ] found in their research that a higher level of irisin is associated with a better metabolic profile of obese people.…”
Section: Discussionmentioning
confidence: 99%